“BEST” Test – The game changer of noninvasive cardiac imaging - Chandra Shekara Reddy; Arun Srinivas; Nithin Bharadwaj; Samuel; Guru Prasad; Siddarth Kumar Chawath (Heart India, 2025)
Introduction: Advanced echocardiography should be accurate, versatile, comprehensive, and cost-effective that can be incorporated into daily clinical care. Methods: We randomly selected 156 two-dimensional (2D) echo subjects for “BEST Test” – To convert 2D to three-dimensional (3D) slice during offline process using specific steps. From this pool, we had 28 randomly selected subjects for substudy linear measurement analysis. Each had three sets of values by direct measurement, before and after 3D slice. Between the methods, correlation analysis and Bland–Altman scatter plot analysis was done. Results: Out of 154, 147 were male (95.5%) with a mean age of 48.7 years (16–85 years). Following specific steps, all 2D Echo clips were converted into realistically rendered realtime “3D Slice” data, depends on quality of 2D echo images. From correlation analysis, most measurement methods show a positive correlation. Maximum with left atrium measurements between Methods 2 and 3 (r2= +0.66) and least with right atrium measurements between Methods 1 and 2 (r2= −0.17). Bland–Altman analysis reports the least mean of −14.5 (95% confidence interval [CI]: −11.5–−17.5) for left ventricular internal diameter at end-diastole and maximum mean of −1.1 (95%CI: +0.3–−2.4) for posterior wall diameter measurements with Methods 1 and 3. The range of agreement varies. Conclusion: “BEST” Test from Blender 3D Software can be used as an offline imaging tool for 2D echo because it qualifies the features of an ideal tool. The complete process can be customizable and reproducible at zero cost. Statistical significance and relationship were noted and established.